Influence of geometry of the impenetrable electrodes on process of formation of the current crisis in the plasma accelerators - Kozlov, A.N. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
This paper reports the results of the numerical studies of the axisymmetric flows in the plasma accelerators with the impenetrable equipotential electrodes of the various geometries. The calculations were performed using the two-dimensional two-fluid magnetohydrodynamic model taking into account the Hall effect and the conductivity tensor of the medium. The numerical experiments have allowed to reveal the influence of the electrode form on effect of occurrence of the current crisis. Представлены результаты численных исследований осесимметричных потоков в плазменном ускорителе с непроницаемыми эквипотенциальными электродами различной геометрии. Расчеты выполнены в рамках двумерной двухжидкостной МГД-модели с учетом эффекта Холла и тензора проводимости среды. Численные эксперименты позволили выявить влияние формы электродов на эффект возникновения кризиса тока. Представлено результати чисельних досліджень вісесиметричних потоків у плазмовому прискорювачі з непроникними еквіпотенціальними електродами різної геометрії. Розрахунки виконано в рамках двовимірної дворідинної МГД-моделі з урахуванням ефекту Холу і тензора провідності середовища. Чисельні експерименти дозволили виявити вплив форми електродів на ефект виникнення кризи струму. The work has been executed at the financial support of Russian Foundation of Basic Research (grant 09-01-12056) and Russian Academy of Science (the program No. 14 (1) of Presidium RAS).